Health-centered agency and perceived barriers to health achievement among blind and visually impaired women - mohammad ganji; narges nikkhah; fateme hami kargar; masoud ghafari (پژوهشنامه مددکاری اجتماعی, 2022)
Different social groups each make efforts to achieve health, and due to their social status, they also face obstacles to achieving health. Among them, blind and combination women also have unique experiences in They have this background. This phenomenological study analyzes the efforts of blind and partisan women in the context of their life experience and also the obstacles to their progress in Kashan. In this regard, using purposive sampling with the criterion of theoretical saturation, 25 blind and combo women were selected for in-depth interviews. The interviews were then analyzed using Brown and Clark thematic analysis. After extracting the appropriate codes, two main themes with the titles of health-centered agency and perceived barriers to health have been obtained. Health-oriented agency includes actions and actions that are in the field of awareness of individuals and occur to maintain, improve or promote health. And has the sub-themes of basic health presuppositions, conscious prevention in order to maintain health, reconstruction and treatment, and measures that are detrimental to health. Perceived health barriers also refer to macro-social categories that restrict the realization of health in blind and visually impaired women outside the will of individuals and contain sub-themes of economy-based health, harassing behaviors. Society is a disabling social context and a challenge to the institution of treatment and the passive family.